2015
DOI: 10.3390/polym7020266
|View full text |Cite
|
Sign up to set email alerts
|

P(MMA-EMA) Random Copolymer Electrolytes Incorporating Sodium Iodide for Potential Application in a Dye-Sensitized Solar Cell

Abstract: Abstract:Polymer electrolytes based on 90 wt% of methyl methacrylate and 10 wt% of ethyl methacrylate (90MMA-co-10EMA) incorporating different weight ratios of sodium iodide were prepared using the solution casting method. The complexation between salt and copolymer host has been investigated using Fourier transform infrared spectroscopy. The ionic conductivity and thermal stability of the electrolytes were measured using impedance spectroscopy and differential scanning calorimetry, respectively. Scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Research in sodium ion polymer electrolyte has been increasing in recent years. A few attempts have tried polymer electrolytes based on sodium ion complexed films (Dzulkurnain et al, 2015). The main advantage of using sodium metal ion is its availability in abundance at a cheaper cost than lithium.…”
Section: Introductionmentioning
confidence: 99%
“…Research in sodium ion polymer electrolyte has been increasing in recent years. A few attempts have tried polymer electrolytes based on sodium ion complexed films (Dzulkurnain et al, 2015). The main advantage of using sodium metal ion is its availability in abundance at a cheaper cost than lithium.…”
Section: Introductionmentioning
confidence: 99%
“…It could be observed that the FTIR spectra shows several important peaks assigned to C=O stretching at (1720-1731 cm -1 ) (Fig. 4(a)) [16,20], ν a -(C-O-C) at (1147-1151 cm -1 ) (Fig. 4(b)) [20,22] and O-C 2 H 5 at (1443-1451 cm -1 ) (Fig.…”
mentioning
confidence: 99%
“…In our previous work [15], the modification of polymer host was done using solvent-free UV-curing technique by copolymerizing ethyl methacrylate (EMA) with methyl methacrylate (MMA) monomer. The copolymer was then added with sodium iodide (NaI) for SPEs preparation.…”
mentioning
confidence: 99%
See 2 more Smart Citations